Brainstem micro-abscesses caused by Burkholderia pseudomallei in a 10-month-old infant: a case report. (3rd July 2017) - Prasanna Kumar, M.; Krishnamurthy, Sriram; Venkateswaran, V. S.; Mahadevan, Subramanian; Lalitha, M.; Sistla, Sujatha; Nagarajan, K.
Abstract : Melioidosis is an uncommon tropical infectious disease caused by Burkholderia pseudomallei . Neurological complications of melioidosis are extremely uncommon in infants. A 10-month-old girl is described who presented with disseminated melioidosis with subcutaneous nodules, arthritis, hepatomegaly and a lung cavity, and developed a left medial rectus palsy. Cranial MRI demonstrated mid-brain, pontine and basal ganglia micro-abscesses. Therapy with meropenem and cotrimoxazole led to resolution of the medial nerve palsy. At 5-month follow-up, the child had no residual neurological deficits.